Body composition using bioelectrical impedance analysis in elite young soccer players: the effects of age and playing position - Torres-Luque, G.; Calahorro-Cañada, F.; Lara-Sánchez, A. J.; Garatachea, N.; Nikolaidis, P. T. (Sport Sciences for Health, 2015)
Most of the research in body composition of young soccer players has used anthropometric techniques as assessment methods. On the other hand, there is lack of data concerning bioelectrical impedance analysis (BIA) in young soccer players, a method which might provide more detailed information on body composition than the traditional anthropometric techniques. Purpose: Therefore, the aim of this study was to examine body composition assessed by BIA of young soccer players with regard to their age and playing position. Methods: We examined the body composition of 65 soccer players (age 15.2 ± 0.2 years, weight 63.3 ± 9.4 kg, height 171.5 ± 8.3 cm and training experience of 9.0 ± 1.5 years), classified into three age groups (U14, ~13 years; U16, ~15 years; and U18, ~17 years) and four playing positions (goalkeepers, defenders, midfielders and forwards). Results: U14 showed lower weight, BMI, intracellular and extracellular water, protein, mineral mass, basal metabolism and all parameters of body balance (p < 0.001) than U16 and U18. Within each age group, there were differences between forwards and defenders (p < 0.05). Also, we found differences between defenders of different age groups; defenders in the younger group had lower values in all parameters than their older counterparts and the same trend was noticed in midfielders. Conclusions: Our findings with regard to positional differences in weight, height, BMI and body fat percentage were in agreement with previous studies. However, what is novel is that we observed corresponding differences in the cellular level, which should be confirmed by future studies. ABSTRACT FROM AUTHOR